Exploring the diagnostic utility of genome sequencing for fetal congenital heart defects. (27th April 2022) - Cao, Y.; Chau, M. H. K.; Zheng, Y.; Zhao, Y.; Kwan, A. H. W.; Hui, S. Y. A.; Lam, Y. H.; Tan, T. Y. T.; Tse, W. T.; Wong, L.; Leung, T. Y.; Dong, Z.; et al.
Abstract: Objective: The diagnostic yield for congenital heart defects (CHD) with routine genetic testing is around 10%–20% when considering pathogenic CNVs or aneuploidies as positive findings. This is a pilot study to investigate the utility of genome sequencing (GS) for prenatal diagnosis of CHD. Methods: Genome sequencing (GS, 30X) was performed on 13 trios with CHD for which karyotyping and/or chromosomal microarray results were non‐diagnostic. Results: Trio GS provided a diagnosis for 4/13 (30.8%) fetuses with complex CHDs and other structural anomalies. Findings included pathogenic or likely pathogenic variants in DNAH5, COL4A1, PTPN11, and KRAS . Of the nine cases without a genetic etiology by GS, we had outcome follow‐up data on eight. For five of them (60%), the parents chose to keep the pregnancy. A balanced translocation [46, XX, t(14; 22)(q32.33; q13.31)mat] was detected in a trio with biallelic DNAH5 mutations, which together explained the recurrent fetal situs inversus and dextrocardia that was presumably due to de novo Phelan‐McDermid syndrome. A secondary finding of a BRCA2 variant and carrier status of HBB, USH2A, HBA1/HBA2 were detected in the cohort. Conclusions: GS expands the diagnostic scope of mutation types over conventional testing, revealing the genetic etiology for fetal heart anomalies. Patients without a known genetic abnormality indicated by GS likely opted to keep pregnancy especially if the heart defect could be surgically repaired. We provide evidence to support the application of GS for fetuses with CHD. Key points: What's already known about this topic? The diagnostic yield of exome sequencing for fetuses with structural abnormalities after undiagnostic conventional testing is 20%–30%. The diagnostic yield of genome sequencing for fetal heart defects is not established. What does this study add? This study demonstrated that genome sequencing has a diagnostic yield of 30.5% in fetuses with congenital heart defects (CHD) and is even higher in cases with complex CHD and syndromic abnormalities. Pulmonary stenosis with other structural anomalies is more commonly associated with a genetic diagnosis, while a molecular genetic diagnosis is less frequently achieved for isolated aortic anomalies. Genome sequencing provided an integrated analysis of a range of mutation types and also detected additional clinically relevant genetic findings such as chromosomal structural rearrangements.